Union Pacific : Volume I, 1862-1893 - Klein, Maury (Book collections on Project MUSE., 2006)
The second volume in the history of the Union Pacific begins after the financial panic of 1893, one of the worst depressions Americans had yet experienced, which pushed the railroad into bankruptcy. Maury Klein examines the complex challenges faced by the Union Pacific in the new century-the expanding role of government and its restrictive regulations, the growth of labor unions, the devastating effects of two world wars, and the growing competition from new modes of transportation-and how, under the innovative and influential leadership of Edward H. Harriman, the Union Pacific again played th.